Correlations between Microscale Indentation Creep and Macroscale Tensile Creep of Polymers - Slouf, Miroslav; Steinhart, Milos; Nemecek, Pavel; Gajdosova, Veronika; Hodan, Jiri (Materials (Basel, Switzerland), 2023)
We compared the results of various microscale indentation creep (microcreep) measurements with macroscale tensile creep (macrocreep) measurements of three common polymers: high-density polyethylene (PE), polypropylene (PP), and polystyrene (PS). The main objective was to verify if the short-term microcreep experiments could predict long-term macrocreep behavior of the selected polymers, whose properties ranged from very soft and ductile (PE) to very hard and brittle (PS). The second objective was to compare several creep predictive schemes: the empirical power law model (PL) and several types of phenomenological elasto-visco-plastic models (EVP). In order to facilitate this task, we developed a universal program package named MCREEP, which fits PL and EVP models to both tensile and indentation creep data. All experimental results and theoretical predictions documented that: (i) regardless of the creep experiment type, both micro- and macrocreep resistance increased in the following order: PE < PP < PS, (ii) the short-term microcreep experiments could be used to predict qualitatively the long-term macrocreep behavior, and (iii) the simple empirical power law model yielded better predictions of long-term creep behavior than the more sophisticated elasto-visco-plastic models.
Keywords: polymers; viscoelasticity; microindentation; tensile creep; indentation creep